A framework for targeting water, sanitation and hygiene interventions in pastoralist populations in the Afar Region of Ethiopia - Whitley, L.; Hutchings, P.; Cooper, S.; Parker, A.; Kebede, A.; Joseph, S.; Butterworth, J.; van Koppen, Barbara; Mulejaa, A. (Elsevier, 2019)
Globally, many populations face structural and environmental barriers to access safe water, sanitation and hygiene (WASH) services. Among these populations are many of the 200 million pastoralists whose livelihood patterns and extreme environmental settings challenge conventional WASH programming approaches. In this paper, we studied the Afar pastoralists in Ethiopia to identify WASH interventions that can mostly alleviate public health risks, within the population's structural and environmental living constraints. Surveys were carried out with 148 individuals and observational assessments made in 12 households as part of a Pastoralist Community WASH Risk Assessment. The results show that low levels of access to infrastructure are further compounded by risky behaviours related to water containment, storage and transportation. Additional behavioural risk factors were identified related to sanitation, hygiene and animal husbandry. The Pastoralist Community WASH Risk Assessment visually interprets the seriousness of the risks against the difficulty of addressing the problem. The assessment recommends interventions on household behaviours, environmental cleanliness, water storage, treatment and hand hygiene via small-scale educational interventions. The framework provides an approach for assessing risks in other marginal populations that are poorly understood and served through conventional approaches.